Current perspectives on learning disabilities - Burkhardt, Sandra A.; Obiakor, Festus E.; Rotatori, Anthony F. (Advances in special education ;, 2004)
This book addresses prominent trends in learning disabilities in a systematic and comprehensive manner. The book's major premise focuses on the early identification and intervention of learning disabilities which can positively impact a child's academic performance by making achievement possible. Critical information is discussed to prevent undetected learning disability which may lead even an older student to struggle with poor grades, low self-esteem, loss of interest in higher education, and reduced employment. The book presents current knowledge based information on forces outside of the school that impact the field of learning disabilities such as, advances in evaluation and testing, diagnostic imaging of the functioning brain, evolving ways of conceptualizing learning disabilities that include multicultural perspectives, challenges to conventional views of intelligence and new federal laws that place performance demands upon schools. Additionally, instructional best practice approaches and new technology is provided that should enhance the academic teaching of students. There is even a chapter on a model inner city program that discusses teaching of students with severe learning difficulties. Finally, there is a chapter on the role that school counsellors play in planning for college and careers in a climate of societal expectation that promotes a college education as an obtainable goal for students with learning disabilities. The book is valuable to general and special education teaches, school psychologists, teacher educators, practicing mental health clinicians, and school and career counsellors. A secondary audience is graduate students in special education and counselling graduate programs who need a comprehensive resource book on current trends and best practices.